EFFECTS OF DROUGHT STRESS ON PLANT GROWTH PARAMETERS, MEMBRANE DAMAGE INDEX AND NUTRIENT CONTENT IN COMMON BEAN GENOTYPES - T. Kabay1; C. Erdinc; S. Sensoy (Journal of Animal and Plant Sciences, 2017)
Common bean (Phaseolus vulgaris L.) is an important crop in both Turkey and the world. Drought is one of the important abiotic stress factors limiting the quality and quantity of common bean. This study was conducted to determine the drought-tolerant and susceptible common bean genotypes in Lake Van Basin of Turkey. Total 48 bean genotypes consisted of 40 genotypes from Lake Van Basin, 6 from different parts of Turkey and 1 drought susceptible variety-Zulbiye and 1 drought tolerant variety-Yakutiye. The drought experiment was designed as completely randomized plot with 4 replicates in plastic greenhouse conditions. The four-week-old bean seedlings were subjected to drought stress by completely stopping irrigation for 8 days compared to control seedlings. The investigated traits were growth rate, fresh and dry shoot weights, fresh and dry root weights, stem diameter, area and number of leaves, leaf relative water content (LRWC), membrane damage index (MDI), and ion contents (K, Ca and Na) beside the 0-5 visual scale assessment of drought. At the end of the study, it was determined that plant growth and development of the bean genotypes were negatively affected by drought; however, the studied bean genotypes reacted variously to this stress factors. The genotypes V7, V15, V33, V82, V89 and V-A1 were found to be drought sensitive as the variety Yakutiye, while the genotypes V21, V62, V69, V71, V86, V95 and T7 were found to be drought tolerant as the variety Zulbiye.
Keywords: Drought stress; Phaseolus vulgaris; Tolerance; Lake Van Basin